Profitability and standard gross margin at sheep - Lidia Iurchevici (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
In Romania, must pay a particular attention to adapt the systems of sheep breeding and exploitation with the EU requirements. At the same time, it is necessary to protect and stimulate those characteristics of growing and exploitation of sheep that have competitive advantages on the quality of products obtained. It is important that the technological solutions adopted in the growing and exploitation of sheep to answer all product quality requirements, at European standards. The main objective of this paper is to provide technical - economic solution for sheep breeding to achieve a rate of return that would allow farmers to continue production activity in terms of economic efficiency. To facilitate analysis of the economic results obtained in the farming carried out and the structural characteristics of farms in our country, it is necessary to apply the Community methodology for determining the standard gross margin (SGM), as scientific support for technical - economic orientation.
Keywords: 330; sheep; economic efficiency; costs; standard gross margin